2023
DOI: 10.7759/cureus.36121
|View full text |Cite
|
Sign up to set email alerts
|

Motor Band Sign in Primary Lateral Sclerosis: A Case Report Proposing the Need for an Imaging Biomarker

Abstract: Motor neuron disease is a degenerative condition involving both upper motor neurons (UMN) and lower motor neurons (LMN). While amyotrophic lateral sclerosis (ALS) is an overlap of upper and lower motor neuron involvement, primary lateral sclerosis (PLS) is predominantly an upper motor neuron involvement with lower motor involvement seen in the later stages of illness. Diagnostic criteria rely on clinical features and electrodiagnostic tests such as electromyography (EMG). EMG predominantly helps in determining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
1
0
Order By: Relevance
“…Newcastle-Ottawa scale Cochrane risk of bias Kwan et al [13] Good quality-8/9 stars Low risk of bias Chakraborty et al [2] Fair quality-5/9 stars Moderate risk of bias due to no blinding Boll et al [10] Good quality-7/9 stars Low risk of bias Boll et al [45] Good quality-8/9 stars Low risk of bias Roeben et al [9] Good quality-7/9 stars Low risk of bias Prabhu and Sajja [5] Fair quality-4/9 stars High risk of bias due to no blinding, no control group Budhu et al [17] Fair quality-5/9 stars Moderate risk of bias due to no blinding Makkawi et al [24] Fair quality-6/9 stars Moderate risk of bias due to no blinding Pai et al [15] Fair quality-5/9 stars Moderate risk of bias due to no blinding Chung et al [7] Good quality-8/9 stars Low risk of bias Zanovello et al [16] Good quality-7/9 stars Low risk of bias Valaparla et al [46] Fair quality-6/9 stars Moderate risk of bias due to no blinding…”
Section: Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Newcastle-Ottawa scale Cochrane risk of bias Kwan et al [13] Good quality-8/9 stars Low risk of bias Chakraborty et al [2] Fair quality-5/9 stars Moderate risk of bias due to no blinding Boll et al [10] Good quality-7/9 stars Low risk of bias Boll et al [45] Good quality-8/9 stars Low risk of bias Roeben et al [9] Good quality-7/9 stars Low risk of bias Prabhu and Sajja [5] Fair quality-4/9 stars High risk of bias due to no blinding, no control group Budhu et al [17] Fair quality-5/9 stars Moderate risk of bias due to no blinding Makkawi et al [24] Fair quality-6/9 stars Moderate risk of bias due to no blinding Pai et al [15] Fair quality-5/9 stars Moderate risk of bias due to no blinding Chung et al [7] Good quality-8/9 stars Low risk of bias Zanovello et al [16] Good quality-7/9 stars Low risk of bias Valaparla et al [46] Fair quality-6/9 stars Moderate risk of bias due to no blinding…”
Section: Studymentioning
confidence: 99%
“…64% of patients[16]. Lastly, Valaparla et al identified sulcal hypointensities in T2-w and SWI images in the precentral regions on both sides[46].…”
mentioning
confidence: 98%
“…The sensitivity of SWI is particularly high when it comes to detecting deoxygenated blood and mineral deposits within the brain [4]. The MBS has also been observed in other neurodegenerative movement disorders [1, 5, 6], such as Parkinson's disease [5–7], Alzhimer's disease [5–8], and Huntington's disease [9].…”
Section: Figurementioning
confidence: 99%